2019
DOI: 10.3390/medicines7010001
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in Mycosis Fungoides and Racial Differences in Co-Existent Lymphomatoid Papulosis: A Cross-Sectional Study of 580 Patients in an Urban Tertiary Care Center

Abstract: Background: Mycosis fungoides (MF) is a cutaneous T-cell lymphoma. Previous reports have suggested MF is associated with inflammatory conditions such as psoriasis, increased cardiovascular risk factors as well as secondary neoplasms. Methods: A cross-sectional study of MF patients seen from 2013 to 2019 was performed. Comorbidities were selected based on the 2015 Medicare report highlighting the most common chronic medical illnesses in the United States. Lifetime comorbidity occurrence in patients with MF were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…A total of 692 patients were diagnosed with MF during the same 21 years in our clinic (unpublished data), and the ratio of association of LyP in this MF group was 2.7% (n=19) ( Figure 3 ). In a recently reported large series of MF patients (n=580), the rate for association of LyP was found to be 1.9% [ 19 ]. Interestingly, in the same study, a significant association of LyP among Caucasian MF patients (3%) was reported when compared to African American MF patients (0%) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 692 patients were diagnosed with MF during the same 21 years in our clinic (unpublished data), and the ratio of association of LyP in this MF group was 2.7% (n=19) ( Figure 3 ). In a recently reported large series of MF patients (n=580), the rate for association of LyP was found to be 1.9% [ 19 ]. Interestingly, in the same study, a significant association of LyP among Caucasian MF patients (3%) was reported when compared to African American MF patients (0%) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…LyP has an almost excellent prognosis with a 10-year survival rate of up to 100%, with a variable clinical course ranging from a few to frequent relapses [ 5 ]. However, this good prognosis may change in patients with associated cutaneous and systemic lymphomas [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Possible risk factors for secondary lymphomas and the frequency of this association remain unclear [ 7 , 9 , 10 , 11 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study found that MF was strongly associated with lymphomatoid papulosis, Hodgkin's disease, congestive heart failure, hypertension, and hyperlipidemia compared with healthy controls [11]. Of note, the association between MF and lymphomatoid papulosis was seen in Caucasian and not African American patients [11]. The study provides valuable epidemiologic information on MF that can be used by clinicians managing this condition [11].…”
Section: Epidemiologymentioning
confidence: 68%
“…Given the chronic nature of this disease, comorbid conditions can significantly add to patient burden. Therefore, Kaul et al performed a cross sectional study to evaluate 580 adult patients with diagnosed MF, to identify the common illnesses associated with MF and any racial differences in comorbid disease [11]. This study found that MF was strongly associated with lymphomatoid papulosis, Hodgkin's disease, congestive heart failure, hypertension, and hyperlipidemia compared with healthy controls [11].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation